Nutritional requirements of sheep, goats and cattle in warm climates: a meta-analysis. (5th June 2014) - Salah, N.; Sauvant, D.; Archimède, H.
<x content-type="archive" xml:space="preserve">Abstract</x> The objective of the study was to update energy and protein requirements of growing sheep, goats and cattle in warm areas through a meta-analysis study of 590 publications. Requirements were expressed on metabolic live weight (MLW=LW0.75) and LW1 basis. The maintenance requirements for energy were 542.64 and 631.26 kJ ME/kg LW0.75 for small ruminants and cattle, respectively, and the difference was significant (P<0.01). The corresponding requirement for 1 g gain was 24.3 kJ ME without any significant effect of species. Relative to LW0.75, there was no difference among genotypes intra-species in terms of ME requirement for maintenance and gain. However, small ruminants of warm and tropical climate appeared to have higher ME requirements for maintenance relative to live weight (LW) compared with temperate climate ones and cattle. Maintenance requirements for protein were estimated via two approaches. For these two methods, the data in which retained nitrogen (RN) was used cover the same range of variability of observations. The regression of digestible CP intake (DCPI, g/kg LW0.75) against RN (g/kg LW0.75) indicated that DCP requirements are significantly higher in sheep (3.36 g/kg LW0.75) than in goats (2.38 g/kg LW0.75), with cattle intermediate (2.81 g/kg LW0.75), without any significant difference in the quantity of DCPI/g retained CP (RCP) (40.43). Regressing metabolisable protein (MP) or minimal digestible protein in the intestine (PDImin) against RCP showed that there was no difference between species and genotypes, neither for the intercept (maintenance=3.51 g/kg LW0.75 for sheep and goat v. 4.35 for cattle) nor for the slope (growth=0.60 g MP/g RCP). The regression of DCP against ADG showed that DCP requirements did not differ among species or genotypes. These new feeding standards are derived from a wider range of nutritional conditions compared with existing feeding standards as they are based on a larger database. The standards seem to be more appropriate for ruminants in warm and tropical climates around the world.